Relación de la satisfacción laboral en el desempeño de los empleados de servicios de Aseo de Buenaventura - Valle del Cauca, Año 2020. (2021)
The present research study had the general objective of analyzing the relationship factors between job satisfaction in the performance of the cleaning service employees of Buenaventura 2020, this was developed with a non-experimental, cross-sectional quantitative design. To respond to what was raised in the document, the instrument used to measure job satisfaction was applied Minnesota Satisfaction Questionnaire (MSQ) where seven people belonging to the cleaning staff of the aforementioned company were taken as a sample. To analyze the relationship of these two variables, a descriptive statistical analysis was carried out, which allowed us to identify the level of existing relationship. From the information obtained and the statistical data, it was possible to show the existence of a high level of relationship between these variables.